Charge transport mechanisms and density of interface traps in MnZnO/p-Si diodes - Tascioglu, Ilke; Farooq, W. A.; Turan, Rasit; Altindal, Semsettin; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2014)
MnZnO films were grown onto p-Si substrate by sol-gel spin coating method. The electrical properties of the diodes were investigated at room temperature via the current-voltage (I-V), capacitance-voltagefrequency (C-V-f), and conductance-voltage-frequency (G-V-f) methods by considering the effect of the interface trap density (D-it) and series resistance (Rs) of the diodes. The rectifying ratio (RR) values of undoped and Mn-doped ZnO/ p-Si diodes (at +/- 4 V) were found to be 275 and 2031, respectively. Mn doping decreases leakage current and increases shunt resistance (R-sh). Also, the reasons of discrepancies in barrier height values determined from different methods were discussed. The C-V and G-V measurements were performed at various frequencies. We observe additional contribution to the capacitance at low frequencies due to interface traps which can follow the ac test signal easily. The density of interface traps (D-it) determined from Hill-Coleman method was also presented for making comparison. The D-it values vary from 9.24 x 10(11) to 1.67 x 10(13) eV(-1) cm(-2) and 2.06 x 10(11) to 2.54 x 10(12) eV(-1) cm(-2) for undoped and Mn-doped ZnO/p-Si diodes, respectively. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Undoped and Mn-doped ZnO/p-Si diodes; Frequency and voltage dependent; Series and shunt resistances; Density of interface traps